Strategi Pemasaran Jasa Pendidikan Islam Transformatif Di MTs Diponegoro Plandaan Jombang - Mokh. Fakhruddin. S; Agus Eko Sujianto; Prim Masrokan Mutohar (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
This research aims to identify and analyze the transformative Islamic educational services marketing strategy applied in Diponegoro Plandaan Jombang MTs. Transformative Islamic education is an educational approach that focuses on the development of the character, morals, and spirituality of students in order to promote positive transformation in themselves. MTs Diponegoro Plandaan Jombang, as an Islamic educational institution, has adopted this approach and strives to attract the interest of prospective students as well as retain existing students. The research uses qualitative methods with data collection techniques such as interviews, observations, and document analysis. The results of the research show that MTs Diponegoro Plandaan Jombang have implemented various effective marketing strategies, such as building a positive image of the institution, improving the quality of education, promoting through social media, and engaging with the local community. In the context of transformative Islamic education, marketing focuses not only on the number of students enrolled but also on the positive changes that students can make in terms of character and spirituality. Therefore, these marketing strategies must be linked to real efforts to produce better students in moral and spiritual aspects. This research provides valuable insights for other Islamic educational institutions that want to adopt a transformative approach to their education. By understanding and implementing appropriate marketing strategies, these kinds of institutions can be more effective in attracting students and achieving their transformative Islamic education goals.